"Better Retail, Better World": A commentary on British retailers and the sustainable development goals. Issue 2 (26th December 2018) - Jones, Peter; Comfort, Daphne
Abstract : The British Retail Consortium's Better Retail, Better World initiative launched in 2018 and looks to mobilise the retail industry to make a leading contribution to the United Nations Sustainable Development Goals (SDGs). This short commentary paper outlines the features of this initiative and offers some reflections on some of the challenges British retailers seem likely to face in looking to contribute to the achievement of the SDGs. These challenges include the strategic prioritisation of SDGs, issues of measurement and metrics, communicating the retailers' position on the SDGs to consumers and the stakeholders, the retailers' financial commitment to the SDGs within a difficult trading environment, and fundamental tensions between sustainability and economic growth.